2002
DOI: 10.1637/0005-2086(2002)046[0048:vfoecf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors of Escherichia coli from Cellulitis or Colisepticemia Lesions in Chickens

Abstract: This study was designed to compare virulence factors of cellulitis-derived Escherichia coli to colisepticemic E. coli in order to clarify whether E. coli associated with cellulitis comprise a unique subset of pathogenic E. coli. Isolates were tested for serotype, capsule, aerobactin production, colicin production, the presence of the iss gene, and serum resistance. Untypable isolates made up the greatest percentage of each group. Serotypes O2 and O78 were the most commonly identified among both groups of isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 18 publications
2
11
0
3
Order By: Relevance
“…E. coli infections are often considered opportunistic whenever the bacteria of concern display great genetic variation. Limited genetic diversity of E. coli bacteria has been reported associated with acute haemorrhagic septicaemia in turkeys (Olsen et al, 2011a), in E. coli septicaemia lesions following cellulitis in chickens (Jeffrey et al, 2002) and in EPS cases found in free-range layer flocks (Olsen et al, 2011b). Also in the present study, limited genetic variation amongst E. coli colonies from bone marrow of laying hens with EPS was found.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…E. coli infections are often considered opportunistic whenever the bacteria of concern display great genetic variation. Limited genetic diversity of E. coli bacteria has been reported associated with acute haemorrhagic septicaemia in turkeys (Olsen et al, 2011a), in E. coli septicaemia lesions following cellulitis in chickens (Jeffrey et al, 2002) and in EPS cases found in free-range layer flocks (Olsen et al, 2011b). Also in the present study, limited genetic variation amongst E. coli colonies from bone marrow of laying hens with EPS was found.…”
Section: Discussionsupporting
confidence: 58%
“…In some cases, however, E. coli was obtained from well-defined disease and lesions. Examples of such research are a study performed by Olsen et al (2011a) in which the clonality and virulence traits of E. coli associated with haemorrhagic septicaemia in turkeys was examined, studies concerning avian cellulitis (Singer et al, 2000;Jeffrey et al, 2002) and research on MLST and plasmid profile characterization of APEC associated with increased mortality in layers (Olsen et al, 2011b). In the present study we examined E. coli bacteria that also originated from welldefined disease outbreaks and lesions; that is, outbreaks of EPS in laying hens and in which only E. coli bacteria obtained from bone marrow were typed using PFGE and MLST.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have identified iss as occurring commonly among APEC isolates, associated with the presence of a ColV/BM virulence plasmid (19,21,28,44,47,57,58). However, some recent studies involving human E. coli have reported conflicting results regarding the prevalence of iss among different E. coli populations (1,5,20,46,47,53).…”
mentioning
confidence: 99%
“…Serum resistance VGs enable the bacteria to survive outside the gastrointestinal tract and overcome the host defence mechanisms (Johnson et al, 2002b;Lynne et al, 2007;Miajlovic and Smith, 2014;Rocha et al, 2008;Tivendale et al, 2004). These VGs are frequently associated with septicaemia as they assist the bacteria in avoiding being killed by the essential defence mechanisms present in the blood, including complement, antimicrobial peptides and other serum components (Boerlin and Reid-Smith, 2008;Jacobson et al, 1992;Jeffrey et al, 2002;Nolan et al, 2003). Several investigations have reported serum resistance VGs are widespread among APEC in comparison with AFEC and have suggested that these VGs contribute to APEC pathogenicity (Delicato et al, 2003;Dozois et al, 1992;Dziva and Stevens, 2008;Lynne et al, 2007;Mellata et al, 2003;Mellata et al, 2012;Nolan et al, 2002;Ozawa et al, 2008;Rocha et al, 2008;Rodriguez-Siek et al, 2005a;Skyberg et al, 2008;Tivendale et al, 2004;Wooley et al, 1992;Yaguchi et al, 2007;Yang et al, 2004;Zhao et al, 2005).…”
Section: Serum Resistancementioning
confidence: 99%
“…Several VGs have been linked with serum resistance mechanisms and the association of each of the serum resistance VGs with APEC pathogenicity mechanisms have also been independently studied (Nakazato et al, 2009;Rocha et al, 2008). However, limited information is known in regards to the presence of different serum resistance VG combinations and their contribution to APEC pathogenicity (Jeffrey et al, 2002;Nolan et al, 2002;Nolan et al, 2003;Sello, 2012).…”
Section: Serum Resistancementioning
confidence: 99%